Minimally Invasive Surgery in Patients With Intracerebral Hemorrhage: A Meta-Analysis of Randomized Controlled Trials - Hou, Duanlu; Lu, Ying; Wu, Danhong; Tang, Yuping; Dong, Qiang (Frontiers in Neurology, 2022)
Background: Minimally invasive surgery for intracerebral hemorrhage (ICH) has been evaluated in clinical trials. Although meta-analyses on this topic have been performed in the past, recent trials have added important information to the results of the comparison. However, little work has been done to compare the effect of MIS and conventional treatment on patient prognosis, especially mortality. Methods: PubMed, EMBASE, Web of Science, Ovid, China National Knowledge Infrastructure, and ClinicalTrials.gov were searched on May 1, 2021, for randomized controlled trials of MIS for spontaneous ICH. The primary outcome was defined as death at follow-up, while the secondary outcome was defined as death in different comparisons between MIS and craniotomy (CT) or medication (Me). Results: The initial search yielded 12 high-quality randomized controlled trials involving 2,100 patients. We analyzed the odds ratios (ORs) for MIS compared with conventional treatment, including Me and conventional CT. The OR and confidence intervals (CIs) of the primary and secondary outcomes were 0.62 (0.45–0.85) for MIS vs. conventional treatment. We also conducted subgroup analyses and found that the ORs and CIs for MIS compared with that of conventional treatment in the short-term follow-up were 0.58 (0.42–0.80), and, in the long-term follow-up, was 0.67 (0.46–0.98); and found that ORs were 0.68 (0.48–0.98) for MIS vs. CT and 0.57 (0.41–0.79) for MIS vs. Me. Conclusions: This meta-analysis demonstrates that certain patients with ICH benefit in short- and long-term follow-up from MIS over other treatments, including open surgery and conventional Me. Systematic Review Registration:https://www.crd.york.ac.uk/PROSPERO/.